2018
DOI: 10.30892/gtg.22210-297
|View full text |Cite
|
Sign up to set email alerts
|

Local Wisdom of Sabang Island Society (Aceh, Indonesia) in Building Ecological Intelligence to Support Sustainable Tourism

Abstract: Ge eo oJ Jo ou ur rn na al l o of f T To ou ur ri is sm m a an nd d G Ge eo os si it te es s Year X

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 4 publications
0
8
0
2
Order By: Relevance
“…Purchasing activities and considerations such as purchasing recyclable materials rather than single-use materials, encouraging seller firms to partner in recycling, purchasing from local firms, purchasing less hazardous cleansers, and purchasing energy-saving materials are all examples of environmental sustainability in action (Mensah, 2006). Hotels aiming for sustainable performance may then apply transformational approaches to the overall performance of the hotel by concentrating on these areas (Erdogan and Baris, 2007;Aswita et al, 2018;Eshun and Tichaawa, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Purchasing activities and considerations such as purchasing recyclable materials rather than single-use materials, encouraging seller firms to partner in recycling, purchasing from local firms, purchasing less hazardous cleansers, and purchasing energy-saving materials are all examples of environmental sustainability in action (Mensah, 2006). Hotels aiming for sustainable performance may then apply transformational approaches to the overall performance of the hotel by concentrating on these areas (Erdogan and Baris, 2007;Aswita et al, 2018;Eshun and Tichaawa, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of rural development, community-based tourism has been proven to be a successful sustainable development initiative to enhance the well being of people in rural areas (Atanga, 2019;Jaafar et al, 2014;Farsani et al, 2011;Idziak et al, 2015;Strydom et al, 2018;Aswita et al, 2018;Vijulie et al, 2018). Extensive research has also been done on the roles of geotourism in improving the livelihood of people (Adriansyah et al, 2015;Dowling & Newsome, 2018;Farsani et al, 2012;Yuliawati et al, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Current research on rural entrepreneurship are mostly being conducted in developed countries like USA (Newbery & Bosworth, 2014), Malaysia (Dahalan et al, 2015) and Finland (Kibler, 2013). There are also numbers of research on sustainabile community-based tourism like in Ghana (Atanga, 2019), in South Africa (Strydom et al, 2018), Romania (Vijulie et al, 2018), Indonesia (Aswita et al, 2018), and Poland (Idziak et al, 2015), as well as the roles of geoparks in rural development (Adriansyah et al, 2015;Dowling & Newsome, 2018;Farsani et al, 2012;Yuliawati et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Sustainable tourism development (STD) applies elements of sustainable development in the context of tourism and recent years has become a dominant paradigm (Hunter, 1995). In addition, the development of sustainable tourism has also become a strategic issue in every tourism development in each region (Alaeddinoglu & Can, 2011;Andreyanova & Ivolga, 2018;Aswita et al, 2018;Dymond, 1997), including the development of bay tourism (Nel & Binns, 2002;Pham, 2012;Stonich et al, 1995). Although many studies have revealed the importance of sustainable tourism development in the local region, studies of tourism development in the bay area (for example, tourism potential, development concepts, and policy directions) are still few and have not been explicitly discussed.…”
Section: Introductionmentioning
confidence: 99%